HADITH AND ELECTORAL POLITICS: ELITE DISCOURSE AND VOTER MOBILIZATION IN INDONESIA - Adi Pradana, Mahatva Yoga; Berakon, Izra (Al-Qalam, 2025)
This paper examines the constructive practices employed by political elites during elections, particularly through social interactions that shape their political behavior and interests. The study aims to identify political strategies that facilitate consensus between elites and voters, considering various models of social exchange that occur within political processes. In an effort to counter negative perceptions of politics, this research highlights the positive dimensions of elite–voter interactions. Adopting a qualitative approach and drawing upon secondary data from books and scholarly journals, the study analyzes the role of hadith in electoral politics. Hadiths addressing leadership, justice, and deliberation are explored as ethical foundations for understanding political strategies, including compromises made by political elites. The findings reveal that political engagement can generate positive outcomes, such as the formation of social networks that foster political stability. Although political elites are often perceived negatively, their efforts at compromise contribute to conflict mitigation and the balancing of political interests. From the perspective of hadith, politics extends beyond the pursuit of power. It serves as a means to realize the common good. The concept of compromise in voter mobilization should therefore be grounded in the values of justice, deliberation, and unity as taught in hadith. Consequently, politics can be understood as a vehicle for promoting collective welfare, serving the public interest, and aligning with Islamic ethical principles.